2020
DOI: 10.1186/s13287-020-01646-2
|View full text |Cite
|
Sign up to set email alerts
|

Loss of receptor tyrosine kinase-like orphan receptor 2 impairs the osteogenesis of mBMSCs by inhibiting signal transducer and activator of transcription 3

Abstract: Background: Receptor tyrosine kinase-like orphan receptor 2 (Ror2) plays a key role in bone formation, but its signaling pathway is not completely understood. Signal transducer and activator of transcription 3 (Stat3) takes part in maintaining bone homeostasis. The aim of this study is to reveal the role and mechanism of Ror2 in the osteogenic differentiation from mouse bone marrow mesenchymal stem cells (mBMSCs) and to explore the effect of Stat3 on Ror2-mediated osteogenesis. Methods: Ror2 CKO mice were gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 42 publications
5
9
0
Order By: Relevance
“…Ror2 was widely accepted as a transmembrane Wnt receptor in canonical and non-canonical Wnt signaling pathway [26-28]. Mice with conditional knockout of Ror2 in mesenchymal progenitors exhibited shorten limbs [25], which was similar to the phenotype of Stat3 CKO mice in the present study. Moreover, the previous study showed a decrease in the width of the proliferative zones and an increase in the width of the hypertrophic zones in the humerus of Ror2 -/mice, which was highly consistent with our ndings in the proximal ulna of Stat3 CKO mice [29].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Ror2 was widely accepted as a transmembrane Wnt receptor in canonical and non-canonical Wnt signaling pathway [26-28]. Mice with conditional knockout of Ror2 in mesenchymal progenitors exhibited shorten limbs [25], which was similar to the phenotype of Stat3 CKO mice in the present study. Moreover, the previous study showed a decrease in the width of the proliferative zones and an increase in the width of the hypertrophic zones in the humerus of Ror2 -/mice, which was highly consistent with our ndings in the proximal ulna of Stat3 CKO mice [29].…”
Section: Discussionsupporting
confidence: 84%
“…In vivo studies have shown that malfunction of Stat3 led to distinguishable bone abnormality in skeletal system [5,10,24]. Our previous study demonstrated that overexpression of Stat3 rescued the decreased osteoblast differentiation of Ror2-knockdown mBMSCs, suggesting Stat3 could be the downstream molecule of Ror2 [25]. Ror2 was widely accepted as a transmembrane Wnt receptor in canonical and non-canonical Wnt signaling pathway [26-28].…”
Section: Discussionmentioning
confidence: 99%
“…Ror2 was widely accepted as a transmembrane Wnt receptor in canonical and non-canonical Wnt signaling pathway [26][27][28]. Mice with conditional knockout of Ror2 in mesenchymal progenitors exhibited shorten limbs [25], which was similar to the phenotype of Stat3 CKO mice in the present study. Moreover, the previous study showed a decrease in the width of the proliferative zones and an increase in the width of the hypertrophic zones in the humerus of Ror2 −/− mice, which was highly consistent with our ndings in the proximal ulna of Stat3 CKO mice [29].…”
Section: Discussionsupporting
confidence: 83%
“…In vivo studies have shown that malfunction of Stat3 led to distinguishable bone abnormality in skeletal system [5,10,24]. Our previous study demonstrated that overexpression of Stat3 rescued the decreased osteoblast differentiation of Ror2-knockdown mBMSCs, suggesting Stat3 could be the downstream molecule of Ror2 [25]. Ror2 was widely accepted as a transmembrane Wnt receptor in canonical and non-canonical Wnt signaling pathway [26][27][28].…”
Section: Discussionmentioning
confidence: 97%
“…In vivo studies have shown that malfunction of Stat3 led to distinguishable bone abnormality in skeletal system [5,9,11]. Our previous study demonstrated that overexpression of Stat3 rescued the decreased osteoblast differentiation of Ror2-knockdown mBMSCs, suggesting Stat3 could be the downstream molecule of Ror2 [25]. Ror2 was widely accepted as a transmembrane Wnt receptor in canonical and non-canonical Wnt signaling pathway [26][27][28].…”
Section: Discussionmentioning
confidence: 97%